The BIM management handbook - Shepherd, David (Building information modelling professional) (RIBA Publishing, 2016)
An authoritative and practical road map for those implementing and managing BIM workflows. With the 2016 deadline for BIM level 2 fast approaching and the growing realisation of the huge benefits BIM brings these skills are becoming industry essentials. Concentrating on the how rather than the why this will help you to adapt by clearly, and without jargon, explaining standard BIM processes, Government standards and the effective coordination of design, construction and asset information. Spanning both organisational strategy and day-to-day practical tasks it explores bottom line business reasoning as well as potential risks and challenges. This is the go-to guide for BIM Coordinators and Managers, architectural principals, design team leaders and architectural technicians ensuring you are BIM ready' in 2016. It will also be invaluable for Part 3 students getting to grips with BIM strategy and implementation.